Surface modification of activated carbon fabric with ozone, part 1: Kinetics and oxidation degree. Issue 5 (3rd May 2016) - Cataldo, Franco; Putz, Mihai V.; Ursini, Ornella; Angelini, Giancarlo
ABSTRACT: Two samples of activated carbon fabrics (ACF) with very high surface area (>1300 to >1800 m 2 /g) were reacted with ozone inside a closed flask under static conditions. The kinetics of ozone decomposition and reaction with the ACF surface was measured in the gas phase using Fourier transform infrared analysis (FT-IR) spectroscopy. The ozone consumption under these conditions was following the pseudofirst-order kinetics law and was accompanied by the production of CO2 and CO. The ozone-oxidized ACF were studied by FT-IR spectroscopy following the growth of key oxidized functional groups, i.e. phenolic OH, ketone groups intended as carboxyl, lactone, and anhydride, as well as quinone groups as a function of the amount of ozone reacted. The weight uptake of the ACF reacted with ozone was followed gravimetrically. The ACF having >1800 m 2 /g was able to reach a weight increase of 25% of its original weight due to the formation of oxygenated surface functional groups. Raman spectroscopy was used for the evaluation of defective structures formed in ACF because of ozonization reaction.